Committing Theatre: Theatre Radicalism and Political Intervention in Canada - Rifkind, Candida (Labour / Le Travail, 2013)
The article reviews the book, "Committing Theatre: Theatre Radicalism and Political Intervention in Canada," by Alan Filewood.
Keywords: COMMITTING Theatre: Theatre Radicalism & Political Intervention in Canada (Book); Canada; FILEWOOD, Alan; History; Nonfiction; THEATER -- Political aspects; Theater